2020
DOI: 10.2514/1.g004596
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Haptic Feedback System for Flight Envelope Protection

Abstract: Several modern aircraft use a passive control manipulator: a spring-damper system that generates command signals to the flight control computers in combination with a flight envelope protection system that limits pilot inputs when approaching the aircraft limits. This research project aims to increase pilot awareness of this protection system through the use of force feedback on the control device, that is, haptics. This paper describes in detail how the haptic feedback works and when it triggers; another pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The key to calculating flight safety set is to determine the boundary conditions f 0 (x) and seek the optimal solution of equation (11). Suppose the flight states are confined to a rectangular area K = ½V min , V max 3 ½a min , a max 3½u min , u max 3½q min , q max , then the boundary conditions f 0 (x) : R 3 !…”
Section: Safety Set Of Nonlinear Dynamics Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key to calculating flight safety set is to determine the boundary conditions f 0 (x) and seek the optimal solution of equation (11). Suppose the flight states are confined to a rectangular area K = ½V min , V max 3 ½a min , a max 3½u min , u max 3½q min , q max , then the boundary conditions f 0 (x) : R 3 !…”
Section: Safety Set Of Nonlinear Dynamics Systemsmentioning
confidence: 99%
“…The flight safety warning system evaluates the safety of the flight state and feeds safety information back to the pilot in some way. In Van Baelen et al, 11 , the risk-evolution analysis is used determine whether a flight state is safe or not, and the safety of the whole flight space is presented in the form of a cloud chart, which provides vivid and predictive information for the pilot by means of computational flight dynamics. In Van Baelen et al, 11 a haptic feedback system is designed by using force feedback through the control device to provide intuitive information on the state of the aircraft relative to the flight envelope protection.…”
Section: Introductionmentioning
confidence: 99%
“…Exploratory research first investigated a system which provided a change in force gradient near the flight envelope limits, and pilots indicated that it lacked discrete information, a 'tick-on-the-stick', indicating when the protections become active (Lombaerts et al, 2017). Therefore, the first design iteration involved both guidance and discrete haptic feedback (Van Baelen et al, 2020). Although one should ideally feel haptic feedback, the working principles are visualized in this paper using the haptic profile, i.e., the amount of force required on the side stick, to move that side stick to a certain deflection.…”
Section: Guidance and Discrete Feedbackmentioning
confidence: 99%
“…Full details are given in our earlier work, see Ref. [15], only the relevant elements for understanding the current experiment will be explained in this section. Two designs are elaborated which use haptic feedback to communicate the flight envelope protection limits by changing the feel on the control device.…”
Section: Feedback Designmentioning
confidence: 99%